Potential Analysis of Cheese Whey as an Alternative Media Growth for Lactobacillus casei Group - Nur Kusmiyati; Maria Massora; Septian Tri Wicaksono (El-Hayah, 2022)
Cheese processing industry throws a lot of whey into the environment that cause pollution. Whey cheese is known to contain lots of organic matter and lactose which is the main energy source for the Lactobacillus genus. This study aims to determine the effect of using cheese whey media on bacterial cell count, total lactic acid, and total sugar in the Lactobacillus casei group consisting of Lactobacillus casei, Lactobacillus paracasei, and Lactobacillus rhamnosus bacteria. The method used in this study was bacterial culture rejuvenated and propagated on MRSB media for 24 hours. As much as 1% of bacterial culture was inoculated into cheese whey medium and incubated at 37 C for 24 hours. Furthermore, observations were made on the number of bacterial cells, total lactic acid, and total sugar in the L. casei group. The results showed that L. paracasei had the highest number of cells (4.862 CFU/ml), total lactic acid (0.264 mg/ml), and total sugar (93.805 mg/ml) and was not significantly different from L. casei and L. rhamnosus. The cheese whey medium was not significantly different from the positive control (MRSB), however, there was a difference in the growth ability of each isolate on the positive control medium. Based on the research, it was shown that cheese whey media could be used as an alternative medium for the growth of the L. casei group.